2004
DOI: 10.1111/j.1527-5299.2004.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Response to Angiotensin‐Converting Enzyme Therapy in Systolic Heart Failure

Abstract: The treatment of heart failure with angiotensin-converting enzyme inhibitors has resulted in substantial improvements in morbidity and mortality due to heart failure. Varying reports in the literature have suggested that African Americans respond less well to angiotensin-converting enzyme inhibitors, but careful reanalysis of major clinical trials in heart failure, especially the Studies of Left Ventricular Dysfunction (SOLVD), demonstrates a similar mortality benefit for African Americans as for whites. Morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the SOLVD (Studies Of Left Ventricular Dysfunction) study, African-American patients had a poorer prognosis and did not have a reduction in total mortality or hospitalization for HF with enalapril compared with placebo (23). Subsequent reanalysis of the SOLVD dataset that adjusted for ventricular function was able to show only a weak nonsignificant trend toward excess mortality, and a persistent trend in increased hospitalizations for HF among African-American patients (4). There have been a number of trials with ACE inhibitors conducted in the post-infarction setting (6 -10,24 -26).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the SOLVD (Studies Of Left Ventricular Dysfunction) study, African-American patients had a poorer prognosis and did not have a reduction in total mortality or hospitalization for HF with enalapril compared with placebo (23). Subsequent reanalysis of the SOLVD dataset that adjusted for ventricular function was able to show only a weak nonsignificant trend toward excess mortality, and a persistent trend in increased hospitalizations for HF among African-American patients (4). There have been a number of trials with ACE inhibitors conducted in the post-infarction setting (6 -10,24 -26).…”
Section: Discussionmentioning
confidence: 90%
“…The efficacy of neurohormonal antagonists, specifically ACE inhibitors, in African-American patients has been questioned given several clinical trials showing a diminished effect on blood pressure and prevention of HF in African-American patients treated with ACE inhibitors compared with white Americans (13). Additionally, retrospective analyses have suggested that ACE inhibitors are less effective in African Americans with chronic HF based on higher hospitalization rates on treatment for African Americans compared with white Americans (4,14). Prior studies have not examined the effect of angiotensin receptor blockers (ARBs) or the combination of ACE inhibitors and ARBs in African-American HF patients relative to similarly treated white Americans.…”
Section: See Page 1872mentioning
confidence: 97%
See 1 more Smart Citation
“…2,22 African Americans heart failure patients seem to respond to angiotensinconverting enzyme (ACE) inhibitors and beta-blockers in a way similar to white patients. 2,22 Data from the African-American Heart Failure Trial indicated a unique survival benefit from a combination of isosorbide dinitrate and hydralazine among African American heart failure patients. 23 However, the mechanism of such benefit has not yet been established and there is no evidence to suggest that combined vasodilator therapy would not be beneficial among some whites or other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…These data form the basis of the widely debated suggestion that renin-angiotensin system (RAS) blockers are less effective in Black patients than in White patients with HF and reduced ejection fraction (HFrEF) . The above findings are not robust, based on the number of events, the statistical methods used and the inconsistency of the results (for death compared with hospitalization).…”
Section: Introductionmentioning
confidence: 99%